Cultural Interaction Program in Corporate Social Responsibility (CSR) PT. Pertamina : Netnography Study - Akma, Hidayatul; Sokarina, Ayudia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to understand cultural interactions in Pertamina's Corporate Social Responsibility (CSR) program. This research uses an interpretive perspective and netnography as research methodology. Data collection uses a passive approach through multiple online platforms, namely Instagram, TikTok and Facebook. The data that has been collected is then analyzed using coding, noting and abstracting. The research results show that Pertamina's CSR program generates various responses and interactions among the community. First, the view 'without money you are nothing